2005
DOI: 10.1097/00006199-200503000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Nursing Characteristics on 30-Day Mortality

Abstract: Hospital nursing characteristics are an important consideration in efforts to reduce the risk of 30-day mortality of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
220
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(247 citation statements)
references
References 28 publications
13
220
1
7
Order By: Relevance
“…9,10,38 Cutting operating expenses may lead to deficiencies in the quality of care, which patients with more severe diseases, including pneumonia, may be less able to withstand, so they will have higher mortality rates 3,9,10 . Previous studies showed that decreased nursing staff, lower educational levels of nurses or higher proportions of casual/ temporary nurses were associated with higher mortality [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…9,10,38 Cutting operating expenses may lead to deficiencies in the quality of care, which patients with more severe diseases, including pneumonia, may be less able to withstand, so they will have higher mortality rates 3,9,10 . Previous studies showed that decreased nursing staff, lower educational levels of nurses or higher proportions of casual/ temporary nurses were associated with higher mortality [39][40][41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…A number of these studies found an association between a nursing skill mix that has a higher proportion of RNs and better outcomes including lower mortality / failure to rescue (Blegen et al, 2011, Estabrooks et al, 2005, lower rates of infections (Blegen et al, 2011, Cho et al, 2003, McGillis Hall et al, 2004, falls (Blegen and Vaughn, 1998, Donaldson et al, 2005, Patrician et al, 2011, pressure ulcers (Blegen et al, 2011, Ibe et al, 2008, and higher patient satisfaction (Potter et al, 2003). The overall pattern of results is largely consistent, with the only significant contradictory evidence coming from one of the weaker studies which showed that a higher proportion of registered nurses was associated with a higher nurse reported incidence of pneumonia (Ausserhofer et al, 2013).…”
Section: March 2016mentioning
confidence: 99%
“…In Alberta, Canada, researchers studied data from approximately 4800 Canadian nurses in 49 hospitals 12 . Their findings that hospitals where a greater proportion of nurses were educated at the baccalaureate level, the skill mix contained a higher proportion of registered nurses, and nurses reported good working relationships with physicians were hospitals that had lower rates of mortality.…”
Section: Staffing Nurse Educational Level and Patient Mortalitymentioning
confidence: 99%
“…10,12,14,15 A pilot study conducted in Barcelona suggests that the Nursing Work Index is also applicable to hospitals in Spain 18 .…”
Section: Quantifying Organizational Attributesmentioning
confidence: 99%